2004
DOI: 10.1002/cm.20037
|View full text |Cite
|
Sign up to set email alerts
|

Cellular stiffness response to external deformation: Tensional homeostasis in a single fibroblast

Abstract: Stiffness responses of fibroblasts were measured by scanning probe microscopy, following elongation or compression by deformation of an elastic substrate by 8%. The cellular stiffness, reflecting intracellular tension acting along stress fibers, decreased or increased instantly in response to the elongating or compressing stimuli, respectively. After this rapid change, the fibroblasts gradually recovered to their initial stiffness during the following 2 h, and then stabilized. The cells did not show conspicuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 16 publications
7
92
0
1
Order By: Relevance
“…First, it may be due to an elastic response of the actin filaments [25]; second, it may be attributed to the changes in the cellular activities such as enhancement of the contractile force and reinforcement of stress fibers [10,26]. Janmey et al investigated the elastic property of an actin matrigel and showed that more than 10% of the strain was required to yield a 2-fold increase in stress [27].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, it may be due to an elastic response of the actin filaments [25]; second, it may be attributed to the changes in the cellular activities such as enhancement of the contractile force and reinforcement of stress fibers [10,26]. Janmey et al investigated the elastic property of an actin matrigel and showed that more than 10% of the strain was required to yield a 2-fold increase in stress [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the time lapse measurement of stiffness, observation of the tempo-spatial changes in the green fluorescent protein (GFP)-tagged actin filaments in stress fibers [10], measurement of tempo-spatial variations in Ca 2+ [30], and measurement of the local activity of small GTPase RhoA by fluorescent resonance energy transfer (FRET) [31] are useful techniques to investigate the involvement of physiological activities in the stiffness response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations